3D Printing Basic Knowledge and Skills Training for Teachers of SMAN 2 Palopo - Baharuddin, Muhammad Rusli; Fitriani A, Fitriani A (Jurnal IPMAS, 2022)
3-Dimensional printing is a manufacturing technique used to create 3-dimensional products. The tool used is a 3D printer with constituent materials such as plastic, metal and powder. This community service activity uses a 3D printer made from plastic because it is considered more practical and effective for laboratory scale. The training participants were teachers at SMAN 2 Palopo, with the presenters being lecturers at Cokroaminoto University, Palopo. The aim of this community service activity is to introduce and provide training to SMAN 2 Palopo teachers in using 3D printer machines. The training participants provided basic material: using a 3D printer machine, how to install the tool, create a design, transfer the design file to the printer, and so on printing the 3D design. The evaluation process is grouped into four categories, namely understanding the concept, installation and use, machine maintenance and desire for further study. Participants' understanding increased by 1.7 points after attending the training. In the skills of installing and using and maintaining machines, the participants' pretest scores were quite low (1.8 and 2.1 points respectively) and increased quite sharply by 2.5 and 2.1 points after training. Meanwhile, the pretest score for wanting to know 3D printing technology reached 3.4 points and increased after participating in the training to 4.5 points. The evaluation results show that 3D printing technology is not yet well known by the public, especially educational institutions. With this existing training, it is hoped that teachers at SMAN 2 Palopo will be able to know and master 3D printing technology which was developed according to their respective knowledge. Furthermore, these skills can be taught to students through seminars, extracurricular activities or can be included in curricular learning materials.